2019
DOI: 10.1007/s42399-019-0041-z
|View full text |Cite
|
Sign up to set email alerts
|

Rotator Cuff Repair Augmentation Using Osteoinductive Growth Factors

Abstract: Rotator cuff injuries (RCIs) present a major health problem due to high incidences of degenerative tears greater than 3 cm and prevalence of re-tears following surgical procedures. Since healing and functional restoration relies upon bone ingrowth into the tendon, it is hypothesised that sustained delivery of osteoinductive factors including bone morphogenetic proteins (BMPs), specifically BMP2-7, may significantly improve RCI tendon-bone healing. Here, growth factor candidates and delivery mechanisms are revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 116 publications
(136 reference statements)
0
8
0
Order By: Relevance
“…[62] During the repair stage, numerous growth factors are expressed, including transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP), which are essential for cell differentiation into a chondrocyte phenotype in the repair stage of enthesis healing. [63][64][65][66] Therefore, it is reasonable to postulate that the greater the number of MSCs and the longer residence time retained in the footprint during the repair process are, the more MSCs that differentiate and integrate into the repaired tissue. Quantitative analysis further revealed that the area under the curve (AUC) in the moderate density group was 2.4-fold higher than that of the high density group and 16.4-fold higher than that of the low density group (P < 0.05, Figure 4e) during the repair stage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[62] During the repair stage, numerous growth factors are expressed, including transforming growth factor-β (TGF-β) and bone morphogenetic protein (BMP), which are essential for cell differentiation into a chondrocyte phenotype in the repair stage of enthesis healing. [63][64][65][66] Therefore, it is reasonable to postulate that the greater the number of MSCs and the longer residence time retained in the footprint during the repair process are, the more MSCs that differentiate and integrate into the repaired tissue. Quantitative analysis further revealed that the area under the curve (AUC) in the moderate density group was 2.4-fold higher than that of the high density group and 16.4-fold higher than that of the low density group (P < 0.05, Figure 4e) during the repair stage.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the enthesis healing undergoes 3 stages: inflammation (0–7 days), repair (5–14 days) and remodeling (>14 days) . During the repair stage, numerous growth factors are expressed, including transforming growth factor‐β (TGF‐β) and bone morphogenetic protein (BMP), which are essential for cell differentiation into a chondrocyte phenotype in the repair stage of enthesis healing . Therefore, it is reasonable to postulate that the greater the number of MSCs and the longer residence time retained in the footprint during the repair process are, the more MSCs that differentiate and integrate into the repaired tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of PRP in tissue regeneration is a rapidly evolving area for both clinicians and researchers and is being employed in various fields, including osteoarthritis [9], rotator cuff repair [10,11] and bone regeneration [12]. This is because autologous platelet concentrations offer an easy, cost-effective method to obtain the high concentrations of specific growth factors Inadequate immobilisation, yet adequate blood supply.…”
Section: Prp and Its Role In Regenerationmentioning
confidence: 99%
“…Promising candidates for such grafts are electrospun fibre scaffolds consisting of polycaprolactone (PCL; [19,20]. These scaffolds consist of spatially oriented fibres with a very high surface area which is a prerequisite for the possible binding of biologically active molecules and the binding of cells [21,22]. PCL is biodegradable with slow degradation rates in vivo [23,24] and PCL-based materials for medical devices such as Capronor, a subdermal implant for long-term drug delivery [25] or drug delivery systems for glaucoma treatment [26] are already in clinical use or trial.…”
Section: Introductionmentioning
confidence: 99%